Numerical inverse method for calculating heat flux in temperature-sensitive-coating measurement on a finite base. (December 2018) - Cai, Zemin; Liu, Tianshu; Montefort, Javier
Highlights: The numerical inverse heat transfer method is developed and validated through simulations. This numerical method is useful to extract heat-flux fields in temperature-sensitive-coating measurements. The developed method is particularly useful for tests in hypersonic wind tunnels. Abstract: The one-dimensional unsteady heat transfer of a polymer layer on a finite base is studied. A numerical inverse method is developed to calculate heat flux from surface-temperature images obtained using temperature-sensitive coating particularly in high-enthalpy wind tunnels. It is found that the effect of the finite thickness of the base is significant as time increases such that the semi-infinite base assumption made in many methods is no longer accurate in heat-flux calculation. The method developed in this work can take into account the effects of the finite thickness of a base and the temperature-dependencies of the thermal properties of the materials. This method has been validated through simulations and processing the experimental temperature-sensitive-paint (TSP) images.